2017
DOI: 10.5539/ijps.v9n2p1
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Correlation of Family Resilience of Parents with a Child with Autism Spectrum Disorders, Parenting Stress and Social Support

Abstract: Stress is an extremely serious symptom in the care of an autistic child and it deteriorates mainly in women and depending on the seriousness of the autism symptoms. As a result, physical and mental health problems are caused in the children's carers, having as a consequence the attack on family resilience. Social support, standard or non-standard, seems that it can be related to the parents' reduced stress levels as well as to an increase in resilience, even though not all researches agree on this conclusion. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Notwithstanding the challenges faced by parents to individuals with ASD or AS, some studies explored resilience and coping among these parents, describing the positive buffering effect of psychological resilience on parents' ability to cope with stress associated with raising a child with ASD (Halstead et al, 2018;Jack, 2016;Lawhorn, 2019;Pastor-Cerezuela et al, 2015). Resilient parents of children with ASD were more likely to achieve physical and mental health, and to preserve a positive outlook of their life (Kavaoliotis, 2017;Kuhaneck et al, 2015). Furthermore, the relationship between stress and resilience was found to bidirectional; resilience was found not only to promote the ability to cope with stress, it was also found to be enhanced by stress (Lawhorn, 2019;Manicacci, et al, 2019;Waizbard-Bartov et al, https://doi.org/10.15405/epsbs.2021.03.02.43 Corresponding Author: Rachel Haller Selection and peer-review under responsibility of the Organizing Committee of the conference eISSN: 2357-1330 430 2019).…”
Section: Challenges and Resilience In Parents To Children's With Asdmentioning
confidence: 99%
See 1 more Smart Citation
“…Notwithstanding the challenges faced by parents to individuals with ASD or AS, some studies explored resilience and coping among these parents, describing the positive buffering effect of psychological resilience on parents' ability to cope with stress associated with raising a child with ASD (Halstead et al, 2018;Jack, 2016;Lawhorn, 2019;Pastor-Cerezuela et al, 2015). Resilient parents of children with ASD were more likely to achieve physical and mental health, and to preserve a positive outlook of their life (Kavaoliotis, 2017;Kuhaneck et al, 2015). Furthermore, the relationship between stress and resilience was found to bidirectional; resilience was found not only to promote the ability to cope with stress, it was also found to be enhanced by stress (Lawhorn, 2019;Manicacci, et al, 2019;Waizbard-Bartov et al, https://doi.org/10.15405/epsbs.2021.03.02.43 Corresponding Author: Rachel Haller Selection and peer-review under responsibility of the Organizing Committee of the conference eISSN: 2357-1330 430 2019).…”
Section: Challenges and Resilience In Parents To Children's With Asdmentioning
confidence: 99%
“…Stress associated with raising a child with ASD prompts parents to find available inner and outer resources and to develop coping strategies in order to restore adequate family functions (Jack, 2016) Studies on resilience among parents of children with ASD, found a variety of protective factors and coping strategies contributing to parental resilience. Both formal community and informal social support were reported as indicators of resilience (Cridland et al, 2014;Kavaoliotis, 2017). Community formal support (e.g., counselling) was found to positively correlate with parental coping, as well as accessing informal support, such as a friend to turn to in a time of need (Lawhorn, 2019), or parental support groups (Jack, 2016).…”
Section: Challenges and Resilience In Parents To Children's With Asdmentioning
confidence: 99%
“…Some studies have suggested that social support plays a crucial role in promoting family resilience [27,28]. A recent meta-analysis found a direct link between social support and the mental health of parents with adolescents suffering from depression [29], indicating that social support may have a positive impact on these family.…”
Section: Introductionmentioning
confidence: 99%